Penfluridol targets septin7 to suppress endometrial cancer by septin7-Orai/IP3R-Ca2+-PIK3CA pathway - Lingyi Song; Huiwen Wu; Xiao Sun; Xiaohu Liu; Xianwu Ling; Wei Ni; Lijuan Li; Beibei Liu; Jinlian Wei; Xiaokang Li; Jian Li; Yudong Wang; et al. (iScience, 2025)
Summary: Phenotypic screening of existing drugs is a good strategy to discover new drugs. Herein, 33 psychotherapeutic drugs in our drug library were screened by phenotypic screening and penfluridol (PFD) was found to exhibit excellent anti-endometrial cancer (EC) activity both in vitro and in vivo. Furthermore, the molecular target of PFD was identified as septin7, a tumor suppressor in EC. In septin7-deficient EC cells and xenograft mouse models, PFD exhibited weaker anti-cancer properties, indicating that septin7 was essential for the tumor inhibitory activity. Notably, PFD could induce cell apoptosis by regulating the septin7-Orai/IP3R-Ca2+-PIK3CA pathway. In addition, PFD attenuates the interaction of septin7-tubulin, thereby inhibiting microtubule polymerization. In summary, this study revealed a target and mechanistic insights into EC therapeutic strategies and identified a potential candidate agent for the treatment of EC.